2020 AHA/ACC Guideline for the Diagnosis and Treatment of Patients With Hypertrophic Cardiomyopathy: Executive Summary: A Report of the American College of Cardiology/American Heart Association Joint Committee on Clinical Practice Guidelines - Ommen, Steve R.; Mital, Seema; Burke, Michael A.; Day, Sharlene M.; Deswal, Anita; Elliott, Perry; Evanovich, Lauren L.; Hung, Judy; Joglar, José A.; Kantor, Paul; Kimmelstiel, Carey; Kittleson, Michelle; et al. (Circulation (New York, N.Y.), 2020)
AIMThis executive summary of the hypertrophic cardiomyopathy clinical practice guideline provides recommendations and algorithms for clinicians to diagnose and manage hypertrophic cardiomyopathy in adult and pediatric patients as well as supporting documentation to encourage their use. METHODSA comprehensive literature search was conducted from January 1, 2010, to April 30, 2020, encompassing studies, reviews, and other evidence conducted on human subjects that were published in English from PubMed, EMBASE, the Cochrane Collaboration, Agency for Healthcare Research and Quality reports, and other relevant databases. STRUCTUREMany recommendations from the earlier hypertrophic cardiomyopathy guidelines have been updated with new evidence or a better understanding of earlier evidence. This summary operationalizes the recommendations from the full guideline and presents a combination of diagnostic work-up, genetic and family screening, risk stratification approaches, lifestyle modifications, surgical and catheter interventions, and medications that constitute components of guideline directed medical therapy. For both guideline-directed medical therapy and other recommended drug treatment regimens, the reader is advised to follow dosing, contraindications and drug-drug interactions based on product insert materials.